A necessary engagement [ reinventing America's relations with the Muslim world - Nakhleh, Emile A. , 1938- (Princeton studies in Muslim politics, 2009)
Offering a balance between analysis, personal memoir, and foreign policy remedies, this book injects much-needed wisdom into the public discussion of long-term US-Muslim relations. This title argues that an engagement with the Muslim world benefits the national interest of the United States